2015
DOI: 10.1186/s13012-015-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

A refined compilation of implementation strategies: results from the Expert Recommendations for Implementing Change (ERIC) project

Abstract: BackgroundIdentifying, developing, and testing implementation strategies are important goals of implementation science. However, these efforts have been complicated by the use of inconsistent language and inadequate descriptions of implementation strategies in the literature. The Expert Recommendations for Implementing Change (ERIC) study aimed to refine a published compilation of implementation strategy terms and definitions by systematically gathering input from a wide range of stakeholders with expertise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
3,017
3
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,754 publications
(3,248 citation statements)
references
References 48 publications
30
3,017
3
13
Order By: Relevance
“…From the experience, we can conclude that disseminating the web-based tool is feasible as it was able to attract potential users, educate them on basic health insurance terms, and make recommendations based on personal information and preference. In addition, it also provides an example of a successful adaption of evidence-based recommendations for implementing change [25,26]. However, future research is needed to investigate the factors that impact online users' information-seeking behaviors when using a public health information tool, as well as to explore the strategies to engage low income populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the experience, we can conclude that disseminating the web-based tool is feasible as it was able to attract potential users, educate them on basic health insurance terms, and make recommendations based on personal information and preference. In addition, it also provides an example of a successful adaption of evidence-based recommendations for implementing change [25,26]. However, future research is needed to investigate the factors that impact online users' information-seeking behaviors when using a public health information tool, as well as to explore the strategies to engage low income populations.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this study actively integrated evidence-based strategies for implementing change [25,26], built coalitions with local stakeholders and communities, and created a feedback loop in developing tool content to transform a research tool to a regular use online tool. Damschroder et al [35] suggested that implementing a research tool in a particular setting requires the preservation of the essential and core elements of the tool, but also the modification of the adaptable elements based on the dissemination settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation research is also inherently multilevel, focusing on individuals, groups, organizations, and systems to change professional behavior and enact service quality improvements [3]. Frequently, the objectives of implementation science include the identification of multilevel variables that impact the uptake of evidence-based practices as well as specific strategies for improving adoption, implementation, and sustainment [4,5]. …”
mentioning
confidence: 99%